Cellular functions and molecular mechanisms of ubiquitination in osteosarcoma - Song, Jiaxun; Yuan, Xiaofeng; Piao, Lianhua; Wang, Jiawen; Wang, Pu; Zhuang, Ming; Liu, Jie; Liu, Zhiwei (Frontiers in Oncology, 2022)
Although some advances have been made in the treatment of osteosarcoma in recent years, surgical resection remains the mainstream treatment. Initial and early diagnosis of osteosarcoma could be very difficult to achieve due to the insufficient sensitivity for the means of examination. The distal metastasis of osteosarcoma also predicts the poor prognosis of osteosarcoma. In order to solve this series of problems, people begin to discover a new method of diagnosing and treating osteosarcoma. Ubiquitination, as an emerging posttranslational modification, has been shown to be closely related to osteosarcoma in studies over the past decades. In general, the cellular functions and molecular mechanisms of ubiquitination during the development of osteosarcoma.